Calculated kindness? The voices of women refugee claimants: accessing pre- and postnatal health care services in Toronto, Ontario - Gateri, Hellen (My University, 2024)
In Canada, refugee claimants are given temporary immigration status, making access to health care services challenging. While the federal government determines the entitlements granted to refugee claimants, provinces are responsible for delivering health care services. This qualitative study conducted in-depth semi-structured interviews with eight refugee claimants and six service providers in Toronto, Ontario. An intersectional theoretical framework was employed to examine the experiences of women refugee claimants and their complicated and often incomplete access to prenatal and postnatal health care services. Findings revealed that delivery of health care services in Ontario created barriers to access and under-utilization of services resulting from intersections of health coverage, immigration status, gender, class, and discrimination.
Keywords: women refugee claimants; prenatal care; postnatal care; healthcare access